The Implementation of Equalitarian Style Communication in Preserving the Towani Tolotang Wedding Culture - Suparman; Kamaluddin Tajibu; Arifuddin Tike (Jurnal Mercusuar, 2023)
This research aims to examine efforts to preserve marriage culture in the Towani Tolotang community, Sidrap Regency. The main focus of the research includes understanding the strategies for preserving marriage culture and the application of "equalitarian style" communication in this context. The research adopts a qualitative approach involving traditional figures, village heads, and the community as key informants. Data collection methods include observation, documentation, and literature review. The data analysis process consists of three stages: data reduction, data presentation, and drawing conclusions. The results show that the equalitarian style of communication plays a crucial role in preserving marriage culture in the Towani Tolotang community. The active participation of traditional figures (Uwa') and their community has proven successful in maintaining the consistency of cultural preservation, as reflected in the implementation of marriage traditions, preserved traditional knowledge, as well as costume and jewelry heritage. The equalitarian style of communication dominates every interaction, emphasizing open and two-way communication, a relaxed atmosphere, and without pressure. In the context of marriage, this facilitates maximum message exchange, strengthens interpersonal relationships, and achieves agreements in various aspects of marriage. This research provides practical implications by emphasizing the importance of developing effective communication approaches to maintain traditions and culture in the Towani Tolotang community. These findings not only contribute theoretical insights into the preservation of marriage culture but also provide practical perspectives that stakeholders can adopt to enhance the sustainability and relevance of traditions in the dynamics of society.